Sweroside‐mediated mTORC1 hyperactivation in bone marrow mesenchymal stem cells promotes osteogenic differentiation. Issue 9 (9th May 2019) - Ding, Yan; Jiang, Huaji; Meng, Biying; Zhu, Biao; Yu, Xiao; Xiang, Guangda
Abstract: This paper aims to probe into the effect of sweroside (SOS) in osteoporosis (OP) and explains mechanisms of its molecular. Applying the ovariectomized (OVX) mouse model investigates the preventive effect of SOS against postmenopausal OP after 3 months of SOS treatment (120 mg/kg/day). Using hematoxylin and eosin (HE) staining and micro computed tomography (CT) observed the morphology of OP in each group. Immunohistochemical staining (IHC) was used to examine osteoblast markers. Experiments in vitro, bone marrow mesenchymal stem cells (BMSCs) from C57/BL6 mice were treated with SOS for 14 days. The staining of alizarin red and alkaline phosphatase activity were measured, and the presentation of osteoblast markers was detected by quantitative reverse transcription PCR. BMSCs were also treated with 1 μg/mL SOS with or without rapamycin, the expression of protein S6 (PS6), P‐mTOR, runt‐related transcription factor 2 (RUNX2), OSX, and osteocalcin (OCN) was detected by Western blotting. Experiments in vivo, HE results show that SOS can alleviate OP, CT results show that there are lower trabecular thickness, bone mineral density, and trabecular number in control OVX mice than those in the OVX + SOS group. IHC results showed that SOS can promote the expression of osteogenic markers and immunofluorescent results show that SOS can promote mTORC1 signal activation. Experiments in vitro revealed that SOS stimulated the activation of the mTORC1 signaling pathway and upregulated RUNX2, OSX, and OCN, rapamycin can reverse it. Our findings demonstrated that differentiated BMSCs into osteoblasts can be promoted by SOS via upregulating the expression of P‐mTOR, PS6, RUNX2, OSX, and OCN. SOS effectively prevented OP by hyperactivation of the mTORC1/PS6 signaling pathway. Abstract : Sweroside (SOS) promoted the differentiation of BMSCs into osteoblasts by upregulating the expression of phospho‐mTORC, protein S6 (PS6), Runx2, OSX, and OCN. SOS effectively prevented OP by hyperactivation of the mTORC1/PS6 signaling pathway.